2018
DOI: 10.18203/2320-1770.ijrcog20184936
|View full text |Cite
|
Sign up to set email alerts
|

Yolk sac and its effects on fetal prognosis

Abstract: Background:The yolk sac is the first extra embryonic structure that becomes sonographically visible within the gestational sac. It provides nutritional, metabolic, endocrine, immunologic, and hematopoietic functions during organogenesis in embryonic life, before placental circulation is established. Spontaneous abortion rates are significantly elevated where the yolk sac volume falls outside the 5 th to 95 th percentile. Abnormal morphological appearance of the yolk sac is also suggestive of serious growth dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
2
0
0
Order By: Relevance
“…Results of the current study are in accordance with the results of the study conducted by Das and Roy (13) , in which 21% of cases (50/100) were aborted, however only 2% of those instances (4% of total cases) had yolk sacs smaller than 2 mm, while in the current investigation, abortion was identified at greater yolk sac sizes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results of the current study are in accordance with the results of the study conducted by Das and Roy (13) , in which 21% of cases (50/100) were aborted, however only 2% of those instances (4% of total cases) had yolk sacs smaller than 2 mm, while in the current investigation, abortion was identified at greater yolk sac sizes.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, in consistence with the current results, in the study by Das and Roy (13) , 3 pregnancies were identified with a big yolk sac (more than 6 mm), and two of those pregnancies ended in abortion. One had a normal, 7 mm morphology and was born at 10 weeks gestation, while the other had an abnormal, 8mm morphology and was born at 5 weeks.…”
Section: Discussionsupporting
confidence: 89%